THE POSITION OF EVIDENCE OF TESTIMONIALS OF WITNESSES WITH DISABILITIES (MINORS) IN RAPE CASES IN THE PROOF PROCESS AT INVESTIGATION LEVEL (Study at the PPA Unit of the Surabaya Police Criminal Investigation Unit - Aprilya, Tarrisa; Puspitosari, Hervina (JARES (Journal of Academic Research and Sciences), 2024)
The purpose of this study was to determine the strength of the evidence of rape victims in cases of rape of children with disabilities and to find out the inhibiting factors of the police against child witnesses with disabilities during the investigation process by the Surabaya Polrestabes. In this study the authors used empirical or sociological legal methods using a qualitative approach. Based on the research results, it is proven that the strength of the testimony of children with disabilities is the same as other normal children as long as the witness has the quality of being a witness and is assisted by an interpreter and psychiatrist who is neutral and impartial. This is due to the quality of the witness, not the physical limitations of the witness. The inhibiting factors of the police towards children with disabilities are witnesses not wanting to tell stories, and being proactive and difficult to control which results in delays in the investigation process, witnesses are not fluent in using sign language, and the unavailability of supporting facilities such as braille, (sign language translators), and refusals persons with disabilities as witnesses.